On determination of mean values of observed quantities according to O. Ya. Orlov - Tyshchuk, M.; Gozhy, A. (Кинематика и физика небесных тел, 2005)
The definition of O.Ya.Orlov for mean values of observed quantities for any epoch suits for application not only in astronomy, and in geophysics, geodesy, meteorology. The method of seasonal decomposition and adjustment Census X-11 for realization of Orlov’s definition in various areas of researches is used.